Attachment and reflective functioning in families with a child on the autism spectrum - Conrad, Charlotte Engberg; George, Carol; Færk, Emil; Jakobsen, Helle; Thomsen, Per Hove; Lauritsen, Marlene Briciet (Frontiers in Psychology, 2025)
The concepts of attachment and reflective functioning are predictors of positive development in children on the autism spectrum. This is the one of the first cross-sectional studies to examine associations between parents’ attachment representations and parental reflective functioning and child attachment in families with children on the autism spectrum. Twenty-eight parents completed the Adult Attachment Projective Picture System and questionnaires of Maternal Perception of Child Attachment and Parental Reflective Functioning regarding their child on the autism spectrum and when applicable a typically developing sibling. To test any associations between the parents’ attachment and parental reflective functioning and parents’ perception of child attachment, the sample was divided in organized (secure, dismissing and preoccupied combined) as compared with unresolved parents. We found a higher level of the parents’ Interest and Curiosity in their child’s mental states (a parental reflective functioning domain) in the organized as compared with unresolved parents. Also, mothers had significantly higher levels of Interest and Curiosity than fathers. There were no other significant differences regarding the remaining questionnaire domains. Also, there were no significant differences between parents’ rating of child attachment or parental reflective functioning in relation to their child on the autism spectrum compared with their typically developing sibling. The findings suggest that future support may enhance focus on parents unresolved to loss and trauma and fathers. Also, more research is needed to understand the implications of attachment and reflective functioning in families affected by autism.